The Educational Ontology of Traditional Pesantren: Exploring the Essential of Education in Pesantren Al-Maqbul - Sulton, Ahmad; Siddiq, Ahmad (EDUKASIA, 2024)
This research aims to explore why the Pesantren Al-Maqbul continues to maintain a traditional education system from the ontological perspective of educational philosophy. This qualitative research focuses on the mechanisms of community interaction in Pesantren Al-Maqbul. To get the data, the collection techniques employed were through observation, interviews, and documentation. This study resulted in findings that (1) The reason Pesantren Al-Maqbul still insists on maintaining the traditional education system cannot be separated from the educational philosophy ontology; (2) The influence of the ontology foundation of the educational philosophy of the Pesantren Al-Maqbul on its educational goals can be identified from the tendency of monism, which places Allah's revelation in the form of the Qur'an and Hadith as the only authoritative source of knowledge; (3) According to the view of Pesantren Al-Maqbul, knowledge about God, humans, and the universe is obtained from an in-depth reading of the Qur'an and Hadith.